Ultra Processed Foods: A South Asian culinary perspective - Sanjay Kalra; Bharti Kalra; Leepica Kapoor; Nitin Kapoor (Journal of the Pakistan Medical Association, 2024)
There is a vast multitude of foodstuffs available, and health care professionals find it challenging to distinguish between healthy and unhealthy offerings. Recent evidence suggests that ultra processed foods should be avoided, as they are associated with harmful effects on health. This communication defines and describes ultra-processed foods, using the internationally accepted NOVA classification. It uses South Asian examples to make the concept easy to understand for South Asian readers. Keywords: Cuisine, diabetes, diet, medical nutrition therapy, nutrition obesity, overweight, person centred care.